Banding the Right Ventricular Assist Device Outflow Conduit: Is It Really Necessary With Current Devices?. Issue 12 (21st May 2015) - Lo, Casey; Gregory, Shaun; Stevens, Michael; Murphy, Deirdre; Marasco, Silvana
Abstract: Implantable left ventricular assist devices (LVADs) have been adapted clinically for right‐sided mechanical circulatory support (RVAD). Previous studies on RVAD support have established the benefits of outflow cannula restriction and rotational speed reduction, and recent literature has focused on assessing either the degree of outflow cannula restriction required to simulate left‐sided afterload, or the limitation of RVAD rotational speeds. Anecdotally, the utility of outflow cannula restriction has been questioned, with suggestion that banding may be unnecessary and may be replaced simply by varying the outflow conduit length. Furthermore, many patients have a high pulmonary vascular resistance (PVR) at the time of ventricular assist device (VAD) insertion that reduces with pulmonary vascular bed remodeling. It is therefore important to assess the potential changes in flow through an RVAD as PVR changes. In this in vitro study, we observed the use of dual HeartWare HVAD devices (HeartWare Inc., Framingham, MA, USA) in biventricular support (BiVAD) configuration. We assessed the pumps' ability to maintain hemodynamic stability with and without banding; and with varying outflow cannulae length (20, 40, and 60 cm). Increased length of the outflow conduit was found to produce significantly increased afterload to the device, but this was not found to be necessary to maintain the device within the manufacturer's recommended operational parameters under a simulated normal physiological setting of mild and severe right ventricular (RV) failure. We hypothesize that 40 cm of outflow conduit, laid down along the diaphragm and then up over the RV to reach the pulmonary trunk, will generate sufficient resistance to maintain normal pump function.